ANALISIS TINGKAT SIKAP KOGNITIF, AFEKTIF, KONATIF PADA NASABAH PEREMPUAN AKAN BANK SAMPAH MALANG (BSM) - Titik Desi Harsoyo; Etsa Astridya Setiyati; Devina Savero (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2016)
Waste problems becomes a national issue that requires the attention of many disciplines, including marketing. This descriptive study aims to analyze the cognitive, affective, and conative attitude of female members toward Malang Waste Bank (BSM). Uses five box method, it is found that the index of cognitive is very high, reveals that female members have a good knowledge and belief about waste bank, have a good understanding of BSM, gain benefits, feel good for participating in environmental cleanliness. Affective which shows a high index value illustrates that sample are comfortable with the system of depositing litter, proud of their participation, and care for the environment. Conative which produces high index indicates that the members have a positive trend in waste sorting inside the house and collect garbage outside the house, ensuring the availability of waste to deposit, and encourage others to participate. The high value of the indexes on all components of attitude indicates that BSM program seemed to be an alternative solution to deal with household waste problems. This study suggests for local governments in coaching BSM. Besides, it addresses the manager of BSM to educate its members since they are the main source of information for prospective participants. Key words: cognitive, affective, conative, female member, waste bank